Food (in)security communication: a Journal of Applied Communication Research forum addressing current challenges and future possibilities. Issue 2 (3rd March 2020) - Schraedley, Megan K.; Bean, Hamilton; Dempsey, Sarah E.; Dutta, Mohan J.; Hunt, Kathleen P.; Ivancic, Sonia R.; LeGreco, Marianne; Okamoto, Kristen; Sellnow, Tim
ABSTRACT: This forum brings together food, (in)security, and communication. The authors participating in this forum center communication as both process and tool for understanding, mitigating, and making meaning of food (in)security. The nine authors together discuss the role of communication in food (in)security, the central challenges for scholars and practitioners working on food (in)security, and the creative possibilities and impacts influencing the future of food (in)security. The forum produces a call for applied scholars to re-imagine communication frameworks in order to make meaningful differences in their communities.